2016
DOI: 10.3390/ijms17050628
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma bovis MBOV_RS02825 Encodes a Secretory Nuclease Associated with Cytotoxicity

Abstract: This study aimed to determine the activity of one Mycoplasma bovis nuclease encoded by MBOV_RS02825 and its association with cytotoxicity. The bioinformatics analysis predicted that it encodes a Ca2+-dependent nuclease based on existence of enzymatic sites in a TNASE_3 domain derived from a Staphylococcus aureus thermonuclease (SNc). We cloned and purified the recombinant MbovNase (rMbovNase), and demonstrated its nuclease activity by digesting bovine macrophage linear DNA and RNA, and closed circular plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…In vitro studies using transposon mutants disclosed MBOVPG45_0215 as exhibiting the majority of nuclease activity for the DNA substrates tested (Sharma, Tivendale, Markham, & Browning, ). A recombinant form of a second nuclease MBOV_RS02825 (equivalent to MBOVPG45_0310) was shown to degrade the DNA component of NETs and to induce apoptosis of macrophages (Zhang et al., ). The gene encoding this nuclease resides within an operon of genes that likely mediates nucleotide binding and uptake, suggesting a role in nucleotide acquisition also.…”
Section: The Causative Organismmentioning
confidence: 99%
“…In vitro studies using transposon mutants disclosed MBOVPG45_0215 as exhibiting the majority of nuclease activity for the DNA substrates tested (Sharma, Tivendale, Markham, & Browning, ). A recombinant form of a second nuclease MBOV_RS02825 (equivalent to MBOVPG45_0310) was shown to degrade the DNA component of NETs and to induce apoptosis of macrophages (Zhang et al., ). The gene encoding this nuclease resides within an operon of genes that likely mediates nucleotide binding and uptake, suggesting a role in nucleotide acquisition also.…”
Section: The Causative Organismmentioning
confidence: 99%
“…Several M. bovis HB0801 proteins have previously been shown to be secreted proteins with significant functions. For example, MbovNase induces apoptosis [ 14 ]; P27 (MBOV_RS03440) is an immunogenic protein [ 19 ]; MbovP579 can be used as a diagnostic biomarker for M. bovis [ 13 ]; and NADH oxidase is an active enzyme that also functions as an adhesin [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, few secretory proteins of M. bovis have been identified. However, preliminary studies have demonstrated that they play significant roles in inducing immunity and as diagnostic biomarkers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In M . bovis , it was shown to function as cytotoxic, secreted nuclease with the potential to induce apoptosis in macrophages [ 46 ]. In M .…”
Section: Discussionmentioning
confidence: 99%